(untitled) (REGE Revista de Gestão, 2019)
Purpose – The purpose of this paper is to assess whether greater participation of venture capital/private equity (VC/PE) funds in the companies’ capital structure at the moment of initial public offering (IPO) contributes to the reduction in the underpricing of their shares. Design/methodology/approach – Descriptive statistics, correlation analysis, mean difference test and cross-sectional regression were used. The final sample consisted of 89 companies making IPO in Brasil Bolsa Balcão between 2007 and 2017. Findings – The participation of VC/PE funds was shown to mitigate the effect of information asymmetry on managers and shareholders, thus reducing the underpricing of companies at the moment of IPO (H1). However, the expectation that a greater participation of these funds promotes further reduction in a potential underpricing (H2) was not confirmed. Research limitations/implications – One can highlight the small amount of IPOs during the sampling period due to the occurrence of international and national economic crises, as well as the difficulty in obtaining information on the participation of VC/PE funds in the companies’ capital structure. Practical implications – It was observed that information asymmetry had a mitigating effect from the presence of these funds in the companies, which can improve the pricing of their shares, decrease the costs and make volume captions viable for investments, in addition to giving credibility to the market information effectiveness. Originality/value – This study differs from others in that it assesses not only the influence of VC/PE funds on the reduction of the underpricing of IPO shares, but also the participation of these funds in the capital of these companies.